2015
DOI: 10.1136/bmjopen-2014-006914
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smoking restrictions and child exposure to secondhand smoke in cars and homes: a repeated cross-sectional survey of children aged 10–11 years in Wales

Abstract: ObjectiveSmall increases in smoking restrictions in cars and homes were reported after legislation prohibiting smoking in public places. Few studies examine whether these changes continued in the longer term. This study examines changes in restrictions on smoking in cars and homes, and child exposure to secondhand smoke (SHS) in these locations, since 2008 postlegislation surveys in Wales.SettingState-maintained primary schools in Wales (n=75).ParticipantsChildren aged 10–11 years (year 6) completed CHETS (CHi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
2
27
1
Order By: Relevance
“…While smoking rates have declined at the population level, parental smoking continues to be highly concentrated in more deprived families [4,5]. In the present study, half of children from the poorest families reported that a parent figure smoked, three times as many as for children from the most affluent families.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…While smoking rates have declined at the population level, parental smoking continues to be highly concentrated in more deprived families [4,5]. In the present study, half of children from the poorest families reported that a parent figure smoked, three times as many as for children from the most affluent families.…”
Section: Discussionmentioning
confidence: 42%
“…Smoking rates have declined substantially in recent years [2], with progressively comprehensive tobacco control strategies acting to de-normalise smoking [3]. However, many parents continue to smoke, with parental smoking particularly common among less affluent families [4]. Given the strong intergenerational transmission of both socioeconomic status and smoking [5], smoking remains a major contributor to the intergenerational reproduction of health inequalities [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Moore et al 73 found that legislation disallowing smoking in public places did not appear to influence social inequalities in ESHS in Wales. A study from Taiwan,62 however, indicated that the expansion of smoke-free legislation reduced inequalities in ESHS across educational but not income groups.…”
Section: Discussionmentioning
confidence: 99%
“…The UK and parts of the USA, Canada and Australia have recently implemented smoking bans for cars that carry children. Research has shown that secondhand smoke exposure in cars can still be substantial, in particular among low SES families, but that it decreased after the implementation of such bans (Elton-Marshall, Leatherdale, Driezen, Azagba, & Burkhalter, 2015;Moore et al, 2015). Smoking in restaurants and workplaces is already prohibited in the Netherlands, but our results imply that designated smoking rooms could be also banned in such environments.…”
Section: Implications For Tobacco Control Policies In the Netherlandsmentioning
confidence: 64%